BERMAIN PERSEPSI DAN TANDA - Adam Wahida (SURYA SENI, 2008)
Playing with Perception and Sign. The art creation aims at making art works based on the spirit of playing with perception and sign, criticizing mass  culture phenomena and giving new alternative in the creative process of making visual arts. The author uses the approach of lateral thinking method, brainstorming and playing in making the art work. The creating stages include exploration, improvisation and forming. The exploration is conducted to directly gather the information of mass culture in both printed or electronic media. The improvisation is made to ﬁnd out various possible ideas and concepts found in the exploration stage, while the forming stage is conducted to materialize the concept into theplanned art work. The spirit of playing in the creating process of the art work can bring mental enlightenment and joyful and pleasing atmosphere. The playing with perception and sign can help construct idea and open freedom space that results in variousalternative manifestations not bound by conventional and standard norms.Playing with perception and sign enables free selection of cultural signs in order to construct the perception building. The resulting work is two-dimension painting with realistic painting technique. The painting represents the perception of thephenomena and the sign of the mass culture, while its subject matter may be classiﬁ ed into some categories such as fashion trend phenomena, idol, communication technology, consumerism, and education as the symbol of prestige andappearance dominance. Keywords: playing, perception, sign, and mass culture